(untitled) (Research, Society and Development, 2022)
The public’s interest and enthusiasm for several scientific topics, namely those related to astronomy, is growing and increasingly widespread. For the past 400 years, since Galileo, astronomers have sought to observe and interpret the universe, building ever more powerful and accurate telescopes. These incredible instruments extend the potential of one of our most important senses, the vision, pushing it towards new limits and therefore transforming and enhancing our understanding of the cosmos. The Hubble space telescope exerts a particular fascination on the public of all ages. It strongly contributes to the dissemination of science and astronomy through the presentation of images that delighted the general public. This document results from a bibliographic and documental review. It aims to present an overview of the contributions from the technological development in the dissemination of the history of astronomy, offering not only a reflection on this legacy, but also the continuity perspective of this history that undeniably keeps challenging humankind.